Teaching Student-Centred Podcasting: Practice-Based Research and Relational Ethnic Studies in The Alchemist Manifesto Podcast "The Seeds, the Soil and the Cyber Garden" Series - Obando, Mario Alberto; Topete, Daniel (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This essay, along with an accompanying podcast, outlines the goals, pedagogy, and implications of the Alchemist Manifesto Podcast’s three-part special series entitled “The Seeds, the Soil and the Cyber Garden.” We argue that podcasting that centres practice-based research can produce heartfelt, communal, and compassionate digital holistic interventions within and beyond the physical spaces of universities and their itinerant knowledge production and distribution. Based on the cross-campus collaboration between CSU Fullerton and CSU Los Angeles in the spring of 2022, we discuss the collaborative pathways generated by working with graduate students Nancy Ocana, Rosa Maldonando, Diana Ponce, Karla Hernandez, Gregory Esparza, Pedro Reyes, Susana Tapia, Felicia Mora, Pedro Martinez, Francisco Najera, Katherine Batanero, and Caroline Romero. Additionally, the essay outlines the series, which features conversations with contributors Roderick Ferguson and Anita Tijerina-Revilla, and our collective efforts to situate podcasting within critical university studies and relational ethnic studies.